EKSISTENSI PEMBELAJARAN KEPERAWATAN SPIRITUAL PADA MAHASISWA KEPERAWATAN SEBAGAI APLIKASI PROSES ASUHAN KEPERAWATAN SPIRITUAL - Yodang; Nuridah (Universitas Jenderal Achmad Yani Yogyakarta, 2020)
Background: Nurse profession is a profession obtained through higher education of professional nursing and is a profession that has the greatest opportunity to provide comprehensive nursing care services to patients, not only focused on the physical patient, but spiritual needs also take the most important place in helping the patient's healing process. Objective: The purpose of this study is to explore the experience of nursing students in learning spiritual care in the application of spiritual nursing care in the environment of nursing education. Methods: This qualitative research was carried out with a descriptive phenomenological approach through in-depth interviews using structured interview guidelines as a research instrument involving 10 nursing students who were undergoing the process of lecturing the selected extension program with a purposive sampling technique. Results: Data analysis was performed by data abstraction, filtering data, coding and arranging categories, sub themes and themes so that the interpretation of research data through the Collaizi method resulted in 2 main themes. Conclusion: The themes are the learning of spiritual care has not been maximally discussed, and the application of spiritual care nursing in clinical practice has not been well implemented.